Missed diagnosis of lissencephaly after prenatal diagnosis: A case report. Issue 7 (17th February 2023) - Liu, Mengna; Liu, Xiao; Wu, Jiebin; Sha, Jing; Zhai, Jingfang; Zhang, Bei
Abstract : Rationale: Lissencephaly (LIS) is a rare and serious cortical malformation characterized by a smooth or nearly smooth brain surface. With the progress of molecular genetics, platelet-activating factor acetylhydrolase brain isoform Ib is the most frequent type during the fetal period. Here, we report an infant with LIS who was missed although undergoing prenatal diagnosis. We aim to share our experiences and lessons. Patient concerns: A 2-month-old male infant presented recurrent convulsions. Karyotype and copy number variation sequencing were conducted to be normal at the 23-week gestation because of bipedal varus and ventricular septal defect (2.3 mm). After birth, he suffered from epilepsy confirmed by video electroencephalogram exam, meanwhile, computed tomography and magnetic resonance imaging revealed pachygyria. The infant was diagnosed with LIS carrying a de-novo mutation c.817 C > T (p.Arg273 Ter, 138) in exon 8 of platelet-activating factor acetylhydrolase brain isoform Ib (NM_000430) detected by whole-exome sequencing. Diagnoses: Based on the clinical characteristics, imaging, and genetic test findings, the infant was diagnosed with LIS. Interventions: The patient was treated with topiramate and dose was adjusted according to the seizure frequency. Outcomes: The infant had recurrent seizures. The muscle tone of his extremities increased, and he could not look up or turn over actively at the age of 6 months. Lessons: Comprehensive evaluation of a multi-disciplinary team should be recommended for patients with epilepsy and cerebral hypoplasia. Individuals with LIS during the fetal period might be missed due to atypical features. In fetuses with structural abnormalities, if karyotype and copy number variation sequencing are both normal, whole-exome sequencing may be an effective complementary means to detect pathogenic variants.